Corrigendum to “Enhancing bending strength in continuous drive friction welding of PEEK polymer cylinders through the innovative progressively increased welding area method” [Journal of Advanced Joining Processes 10 (2024) 100255] - Chil-Chyuan Kuo; Hua-Xhin Liang; Song-Hua Huang; Armaan Farooqui; Shih-Feng Tseng (Journal of Advanced Joining Processes)
The authors regret missing to add the contract number NSTC 113–2221-E-131-023 to the funding statement.